IDENTIFICATION OF ENDOPHYTE BACTERIA FROM RED BETEL LEAVES (Piper crocatum) WITH 16SrRNA GENE AND ITS ANTIBACTERIAL ACTIVITY - Diza Sartika; Miftahur Rahmi; Queen Anugrahi Rahmadira (DIVERSITAS HAYATI, 2025)
Endophytic bacteria are bacteria that live in plants and produce compounds similar to their hosts, one of which is antimicrobial compounds. Several studies have shown that certain endophytic bacteria can produce chemical compounds that have health effects, especially endophytic bacteria isolated from medicinal plants. Red betel leaves are known to be able to cure various types of diseases. This plant contains secondary metabolites of the flavonoid, alkaloid, tannin, essential oil, and saponin groups where these compounds have antibacterial activity. This study aims to isolate and test the antibacterial activity of endophytic bacteria from red betel leaves against Staphylococcus aureus and Escherichia coli bacteria , as well as to conduct molecular identification using the 16S rRNA gene. The number of endophytic bacteria that were successfully isolated was 4 isolates, namely 1 shoot leaf isolate (PM), 2 young leaf isolates (MM1 and MM2) and 1 old leaf isolate (TM). The results of antibacterial activity testing were carried out on isolates that had been purified using the Kirby-Bauer method , which showed that each isolate had inhibitory activity against the test bacteria Staphyloccocus aureus , namely: PM: 4.03mm, MM1: 12.1mm, MM2: 3.84mm, all of which were classified as weak. While against the test bacteria Escherichia coli did not have antibacterial activity. The results of molecular identification with the 16S rRNA gene showed that the MM1 bacterial isolate was Bacillus thuringiensis .